2004
DOI: 10.1016/s0265-931x(03)00108-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulating transport of non-Chernobyl 137Cs and 90Sr in the North Atlantic–Arctic region

Abstract: The spatial and temporal distributions of the anthropogenic radionuclides 137 Cs and 90 Sr, originating from nuclear bomb testing and the Sellafield reprocessing plants in the Irish Sea, are simulated using a global version of the Miami Isopycnic Coordinate Ocean Model (MICOM). The physical model is forced with daily atmospheric re-analysed fields for the period 1950 to present. Comparison of temporal evolution of observed and simulated concentrations of 137 Cs have been conducted for the regions east of Scot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…3). The obtained transit times are in accordance with earlier observation-based studies (Kershaw and Baxter, 1995;Livingston et al, 1984), as well as model studies (Nies et al, 1998;Gao et al, 2004;Karcher et al, 2004). Furthermore, Brown et al (2002) found that the transit time is 3.5 yr (42 months) for the Sellafield signal to reach the northern coast of Norway based on cross-correlation analysis of observed 99 Tc in the 1990s.…”
Section: Transit Timesupporting
confidence: 89%
See 3 more Smart Citations
“…3). The obtained transit times are in accordance with earlier observation-based studies (Kershaw and Baxter, 1995;Livingston et al, 1984), as well as model studies (Nies et al, 1998;Gao et al, 2004;Karcher et al, 2004). Furthermore, Brown et al (2002) found that the transit time is 3.5 yr (42 months) for the Sellafield signal to reach the northern coast of Norway based on cross-correlation analysis of observed 99 Tc in the 1990s.…”
Section: Transit Timesupporting
confidence: 89%
“…for the northern North Atlantic and the Nordic Seas, will not be given here as these quantities have been addressed in the studies of Furevik et al (2002), Gao et al (2003Gao et al ( , 2004, Nilsen et al (2003), Hatun et al (2005) and Eldevik et al (2005) for model systems closely related to the one used here. In general, the model system has demonstrated skill in simulating the ocean circulation and thermodynamics in the region of interest.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a pioneering work by Prandle (1984), mixing and time-scales of the radionuclide 137 Cs on the European continental shelf was investigated. More recently, it has been shown that the current generation of OGCMs are capable of simulating the large-scale dispersion (Nordic Seas and the Arctic Ocean) of radionuclides from both European reprocessing plants and atmospheric fallout from nuclear bomb testing in a realistic manner (e.g., Karcher et al, 2004;Gao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%